LESIONS OF THE HEMATOPOIETIC SYSTEM IN A PATIENT WITH SYSTEMIC LUPUS ERYTHEMATOSUS AND THE EFFECTIVENESS OF TREATMENT WITH MYCOPHENOLATE MOFETIL - I.A. Mormol; O.A. Borzykh; N.D. Gerasymenko; C. Esanu; L.P. Ozarchuk (Проблеми екології та медицини)
The article presents a clinical case of the use of mycophenolate mofetil in a patient with high activity of systemic lupus erythematosus (SLE) and suppression of hematopoietic systems. The patient had all the characteristic signs of a severe course of SLE with the development of a complication - severe anemia (frequent exacerbations of the main disease, a significant and constant decrease in the number of erythrocytes and the level of hemoglobin in the general blood test against the background of glucocorticosteroid therapy, the severity of clinical symptoms). Damage to the hematopoietic system is characteristic of such patients and prevailed in the clinical picture of the disease and became the direct reason for seeking medical help. The appointment of mycophenolate mofetil made it possible to reduce the activity of manifestations of the main disease, reduce the development of possible complications, and in the future achieve clinical and laboratory remission. The clinical feature of this case is the effective use of mycophenolate mofetil in a patient with high activity of the course of SLE and the constant occurrence of a severe complication - severe anemia, against the background of glucocorticoid therapy. Damage to the hematopoietic system in the patient prevailed in the clinical picture of the disease and became the direct reason for seeking medical help. According to the literature, the use of mycophenolate mofetil in patients gives a positive clinical result in the treatment of such patients: reducing the activity of the course of the main disease, preventing complications, extending the period of clinical and laboratory remission. This approach will improve the quality of life of patients with this group of diseases with the additional advantage of reducing the burden on health care due to the reduction in the frequency of hospitalizations of patients with severe SLE.